Association of Bone Mineral Density to Cerebral Small Vessel Disease Burden. (2nd March 2021) - Kim, Jeong-Min; Park, Kwang-Yeol; Kim, Hye Ryoun; Ahn, Hwa Young; Pantoni, Leonardo; Park, Moo-Seok; Han, Su-Hyun; Jung, Hae-Bong; Bae, Jaehan
Abstract : Objective: To test the hypothesis that bone mineral loss is mechanistically related to cerebral small vessel disease (SVD), we investigated the relationship between bone mineral density and the prevalence and intensity of SVD among patients with stroke. Methods: We analyzed data of 1, 190 consecutive patients with stroke who were >50 years of age and underwent both brain MRI and dual-energy x-ray absorptiometry from the stroke registry of Chung-Ang University Hospital in Seoul, Korea. The patients were categorized into 3 groups according to their bone mineral density (normal, osteopenia, and osteoporosis). White matter hyperintensities, silent lacunes, cerebral microbleeds, and extensive perivascular space were assessed from brain MRI. Multinomial logistic regression model was used to examine the association between osteoporosis and total SVD score. We also recruited 70 patients with stroke to study serum bone turnover markers and microRNAs related to both cerebral atherosclerosis and bone metabolism to understand bone and brain interaction. Results: Osteoporosis was determined among 284 patients (23.9%), and 450 patients (37.8%) had osteopenia. As bone mineral density decreased, total SVD score and the incidence of every SVD phenotype increased except strictly lobar cerebral microbleeds. Multinomial logistic regression analysis showed that osteoporosis was independently associated with severe SVD burden. The levels of microRNA-378f were significantly increased among the patients with osteoporosis and maximal total SVD score and positively correlated with parathyroid hormone and osteocalcin. Conclusions: These findings suggest a pathophysiologic link between bone mineral loss and hypertensive cerebral arteriolar degeneration, possibly mediated by circulating microRNA.